Transducer Type and Design Influence on the Hearing Loss Compensation Behaviour of the Electromagnetic Middle Ear Implant in a Finite Element Analysis. (16th July 2014) - Liu, Houguang; Ge, Shirong; Cheng, Gang; Yang, Jianhua; Rao, Zhushi; Huang, Xinsheng
Abstract : Several types of electromagnetic transducer for the middle ear implants (MEIs) have been developed as an alternative to conventional hearing aids for the rehabilitation of sensorineural hearing loss. Electromagnetic transducer type and design are thought to have a significant influence on their hearing compensation performance. To investigate these effects, a middle ear computational model was constructed based on a complete set of microcomputerized tomography section images of a human ear. Its validity was confirmed by comparing the model predicted motions with published experimental measurements. The result shows that the eardrum driving transducer (EDT) is superior to the floating mass transducer (FMT) in hearing compensation when the transducer mass is small but inferior to the FMT when the mass gets bigger. The incus body driving transducer (IBDT) is the most ineffective type of transducer for hearing compensation. Moreover, the masses of the EDT and the FMT decrease the transducer performance mainly at higher frequencies: the greater the transducer mass, the lower the displacement of the stapes excited by these transducers. On the other hand, the IBDT driving rod stiffness decreases transducer's performance severely at low frequencies and its adverse effect on transducer performance increases with the decrease of the stiffness of the IBDT driving rod.